PENGARUH CIRCUIT TRAINING TERHADAP PENINGKATAN VO2MAX WASIT ASOSIASI PSSI KABUPATEN JOMBANG - Muhammad Ba’tradiansar; Sri Purnami; Sugiyanto Sugiyanto (Jurnal Pendidikan Jasmani)
ABSTRACT: Researchers found that a low VO2 max football referee Association of PSSI Jombang. One way to increase VO2 max is the circuit training. The purpose of this study was to determine the effect of circuit training to VO2 max increase referee Association of PSSI Jombang. In addition, this study to determine the effect of conventional exercise Association of PSSI referee Jombang. Through the research is expected to generate alternative ways to increase VO2 max workout referee Association  of PSSI Jombang. The study design used is an experimental research. Of the 20 semple divided into two groups by means of ordinal pairing matching. Based on the analysis of data, circuit training gave a significant effect on the increase in VO2 max referee Association of PSSI JombangKeywords: Circuit training, VO2 max, football referee.